ChemInform Abstract: A 3‐D Framework Based on Mono‐CopperII Substituted Silicotungstate Units [Cu(dap)2(H2O)]2[Cu(dap)2] [α‐SiW11CuO39]·2H2O. Issue 3 (January 2015) - Luo, Jie; Li, Hailou; Chen, Xinxin; Ma, Jianru; Chen, Lijuan; Zhao, Junwei
Abstract The title compound (dap: 1, 2‐diaminopropane) is hydrothermally synthesized from a mixture of Na10[A‐α‐SiW9O34], CuCl2, LaCl3, dap, and H2O (autoclave, 160 °C, 6 d, 33% yield).